Dar al-Islam revisited : territoriality in contemporary Islamic legal discourse on Muslims in the West - Albrecht, Sarah. (Muslim Minorities, 2018)
Where is dār al-islām , and who defines its boundaries in the 21st century? In Dār al-Islām Revisited. Territoriality in Contemporary Islamic Legal Discourse on Muslims in the West , Sarah Albrecht explores the variety of ways in which contemporary Sunni Muslim scholars, intellectuals, and activists reinterpret the Islamic legal tradition of dividing the world into dār al-islām , the "territory of Islam," dār al-ḥarb , the "territory of war," and other geo-religious categories. Starting with an overview of the rich history of debate about this tradition, this book traces how and why territorial boundaries have remained a matter of controversy until today. It shows that they play a crucial role in current discussions of religious authority, identity, and the interpretation of the shariʿa in the West.